2013 World Congress on Computer and Information Technology (WCCIT) 2013
DOI: 10.1109/wccit.2013.6618670
|View full text |Cite
|
Sign up to set email alerts
|

Biometric secret path for mobile user authentication: A preliminary study

Abstract: In this paper, we study a recent biometric modality for user authentication on mobile devices. The proposed solution is a two-factor user authentication scheme and gives some high guarantees on user's identity. We first use the knowledge of user's password represented by a secret path on a grid composed of 9 points. Second, the behavior of the user while giving its path is analyzed to verify its identity. This solution is implemented as an Android application for mobile devices. Experimental results on an own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Related work addressed verifying user identity with diverse touch measures: Shape-based phone unlock systems were enhanced with an implicit layer using touch sequence matching [1,7,18]. Characteristics of touch strokes from zooming and scrolling were utilised as well [23,58].…”
Section: Touch-based Implicit Authentication and Identificationmentioning
confidence: 99%
“…Related work addressed verifying user identity with diverse touch measures: Shape-based phone unlock systems were enhanced with an implicit layer using touch sequence matching [1,7,18]. Characteristics of touch strokes from zooming and scrolling were utilised as well [23,58].…”
Section: Touch-based Implicit Authentication and Identificationmentioning
confidence: 99%
“…Selection of 12 subjects is backed by a research conducted by Miluzzo et al [20] who conducted their research using 10 subjects and were able to obtain a total of 40,000 tap samples for their analysis having extracted both accelerometer and gyroscope data. Other researchers who also extracted a lot of features from few individuals were Beton et al [21] who were able to obtain 120 intraclass authentication attempts and 1470 interclass attempts (simulating attacks) from 15 subjects. Because of the depth of this research, it was concluded that the 12 subjects selected were going to provide enough data.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, a warp distance of zero means that the subsequent input and reference set are identical. Closer to our study, DTW [22] was used by [16,21] to analyse their features.…”
Section: Methodsmentioning
confidence: 99%
“…They obtained a performance of 19% for the FRR value (False Rejection Rate) and 21% for the FAR (False Acceptance Rate). A method in 2013 has been proposed [21] combining multiple information compared with the Pearson Correlation and the Dynamic Time warping (DTW) methods. The equal error rate (EER) is near 17% which the best result for this biometric modality.…”
Section: Biometric Pattern Based Authenticationmentioning
confidence: 99%